The Effect of Semaglutide on Blood Pressure in Patients without Diabetes: A Systematic Review and Meta-Analysis - Kennedy, Cormac; Hennessy, Martina (MDPI AG, 2023)
(1) Background: Recent advances in the pharmacological treatment of obesity with glucagon-like peptide-1 receptor agonists (GLP-1 RA) highlight the potential to target excess body weight to improve blood pressure (BP). This review aimed to determine the BP reduction in trials of semaglutide for weight reduction in patients without diabetes. (2) Methods: Relevant studies were identified via a search of research databases. Studies were screened to include randomized controlled trials (RCTs) of semaglutide versus a placebo in adults. Pooled and sensitivity analyses were performed, and risk of bias was assessed. (3) Results: six RCTs, with 4744 participants, were included in the final analysis. At baseline, the cohorts in these studies had a mean BP in the normotensive range. The mean difference in systolic BP was −4.83 mmHg (95% CI: −5.65 to −4.02), while that for diastolic BP was −2.45 mmHg (95% CI: −3.65 to −1.24). All included studies were of a high methodological quality. (4) Conclusions: A clinically significant reduction in BP was evident following semaglutide treatment in normotensive populations without diabetes. The effect of semaglutide in those with obesity and hypertension is as yet undetermined. Targeting excess body weight may be a novel therapeutic strategy for these patients.
PUBLISHED
Keywords: Blood pressure; STEP trials; Randomized controlled trials; Weight loss; Semaglutide; Hypertension; Body weight; Obesity; Glucagon-like peptide-1 receptor agonists